Approximation of crystallite size and microstrain via XRD line broadening analysis in TiSiN thin films - Bushroa, Abdul Razak; Rahbari, R.G.; Masjuki, Haji Hassan; Muhamad, Muhamad Rasat (Elsevier, 2012)
In the present work, an approximation method was used to determine both the crystallite size and microstrain from XRD profile of TiSiN thin film deposited on high speed steel substrates. The estimated crystallite size obtained via this approximation method was in good agreement with the resulting microstructure observation using the scanning electron microscope (SEM). The approximation method was used to determine microstrain, and its corresponding compressive stress was related to the result of scratch adhesion measurement of the TiSiN thin film. Comparison of crystallite size and microstrain were investigated using different definitions of line broadening, β. The approximation method was found to be useful in cases when crystallite size and microstrain contributed in the line broadening simultaneously. This research demonstrated the reliability of using the approximation method in determining the resulting crystallite size and microstrain from the XRD line broadening analysis in the TiSiN thin films.